The Economic Impact of Man-Made Tourism Development Towards Local Community in Kota Batu East Java (Case Study: Pasar Parkiran Jatim Park I) - Agfianto, Tomi; Rahman, A Faidlal (E-Journal of Tourism, 2020)
Recently, Tourism becomes a great demand by all people including the millennial group. It makes stakeholders of tourism industries should provide and accommodate the demand of the millennial. The millennial people are close to challenges, technologies, digitals, and something that has excitement. One of tourism concepts which is suitable and highly demand is man-made tourism such as theme park, amusement park, etc. This study aims to identify and analyze the tourism impact that emerges with the existence of man-made tourism activities, because those tourism activities are closely to capitalist monopoly and industrialization. The approach of this research was quantitative method by distributing questionnaires to the tourists who spent their expenditure and local host who received income from the tourism activities. This research was conducted at the Pasar Parkiran tourism destination in Kota Batu East Java which is managed by Jatim Park I. The results of this study explain that the value of Keynesian Income Multiplier (KIM) effect is 0.93. The result shows that tourism activities give positive impact to local host due to the value close to 1.00. The research explains that negative image of mass tourism activities that is monopolized by the company is not totally true, while tourism is managed by the company involving the community as the partner will have a positive impact on both sides. Keywords: Mass Tourism, Man-made Tourism, Tourism Economic Impact, Batu City Tourism Development, Pasar Parkiran.